Transcriptional dynamics of Chitinophaga sp. strain R-73072-mediated alkannin/shikonin biosynthesis in Lithospermum officinale - Ahmad, Muhammad; Varela Alonso, Alicia; Koletti, Antigoni E.; Assimopoulou, Andreana N.; Declerck, Stéphane; Schneider, Carolin; Molin, Eva M. (Frontiers in Microbiology, 2022)
Plants are colonized by a wide range of bacteria, several of which are known to confer benefits to their hosts such as enhancing plant growth and biosynthesis of secondary metabolites (SMs). Recently, it has been shown that Chitinophaga sp. strain R-73072 enhances the production of alkannin/shikonin, SMs of pharmaceutical and ecological importance. However, the mechanisms by which this bacterial strain increases these SMs in plants are not yet understood. To gain insight into these mechanisms, we analyzed the molecular responses of Lithospermum officinale, an alkannin/shikonin producing member of Boraginaceae, to inoculation with R-73072 in a gnotobiotic system using comparative transcriptomics and targeted metabolite profiling of root samples. We found that R-73072 modulated the expression of 1,328 genes, of which the majority appeared to be involved in plant defense and SMs biosynthesis including alkannin/shikonin derivatives. Importantly, bacterial inoculation induced the expression of genes that predominately participate in jasmonate and ethylene biosynthesis and signaling, suggesting an important role of these phytohormones in R-73072-mediated alkannin/shikonin biosynthesis. Detached leaf bioassay further showed that R-73072 confer systemic protection against Botrytis cinerea. Finally, R-73072-mediated coregulation of genes involved in plant defense and the enhanced production of alkannin/shikonin esters further suggested that these SMs could be important components of plant defense in alkannin/shikonin producing plant species.